Molecular Characterization for Karadi Sheep Breed Using Random Amplified Polymorphic DNA Markers - Yousif M. S. N. Al-Barzinji; Ali, Muqdad K. (Sulaimani Journal for Pure and Applied Sciences, 2014)
RAPD-DNA markers were used to study genetic characterization among four locations for Karadi sheep breed in Sulamania governorate. A total of 40 samples were typed using twenty RAPD primers. Nine out of the twenty primers had clear bands, which used to investigate the genetic variations among four locations(Halabjai Taza, Penjwen, Halabja and Sharbazer) of same breed. Out of the nine primers 8 of them are polymorphisms. A total of 119 bands were scored, of which 27 bands (25.05%) were polymorphic and seven of polymorphic band were unique bands. For all location, Nei’s gene diversity, Shannon index and percentage of polymorphic loci are respectively averaged of 0.2361, 0.3415 and 34.60. Using unweighted pair-group method with arithmetic average (UPGMA) dendrogram, the three clusters, the 1st cluster branch consisted of the Karadi sheep in location 1 and 3, the 2nd cluster was including Karadi sheep from location 2 and the 3rd one including sheep from location 4. These results indicated that the Karadi sheep in location 1 and 3 is most genetically distant from the Karadi sheep in location 2 .The dendrograms show that there are moderately genetic diversity among Karadi sheep breed, were ranged from 0.251to 0.541. Based on the high degree of genetic distance among the four locations it is concluded that there are widely area for selection in this breed of sheep.
Keywords: Karadi sheep breed; Genetic distance; RAPDPCR